Immune Responses Induced by the Leishmania (Leishmania) donovani A2 Antigen, but Not by the LACK Antigen, Are Protective against Experimental Leishmania (Leishmania) amazonensis Infection - Coelho, Eduardo Antonio Ferraz (American Society for Microbiology, 2003)
Leishmania amazonensis is one of the major etiologic agents of a broad spectrum of clinical forms of leishmaniasis and has a wide geographical distribution in the Americas, which overlaps with the areas of transmission of many other Leishmania species. The LACK and A2 antigens are shared by various Leishmania species. A2 was previously shown to induce a potent Th1 immune response and protection against L. donovani infection in BALB/c mice. LACK is effective against L. major infection, but no significant protection against L. donovani infection was observed, in spite of the induction of a potent Th1 immune response. In an attempt to select candidate antigens for an American leishmaniasis vaccine, we investigated the protective effect of these recombinant antigens (rLACK and rA2) and recombinant interleukin-12 (rIL-12) against L. amazonensis infection in BALB/c mice. As expected, immunization with either rA2-rIL-12 or rLACK-rIL-12 induced a robust Th1 response prior to infection. However, only the BALB/c mice immunized with rA2-rIL-12 were protected against infection. Sustained gamma interferon (IFN-γ) production, high levels of anti-A2 antibodies, and low levels of parasite-specific antibodies were detected in these mice after infection. In contrast, mice immunized with rLACK-rIL-12 displayed decreased levels of IFN-γ and high levels of both anti-LACK and parasite-specific antibodies. Curiously, the association between rA2 and rLACK antigens in the same vaccine completely inhibited the rA2-specific IFN-γ and humoral responses and, consequently, the protective effect of the rA2 antigen against L. amazonensis infection. We concluded that A2, but not LACK, fits the requirements for a safe vaccine against American leishmaniasis.